2013
DOI: 10.1111/clr.12277
|View full text |Cite
|
Sign up to set email alerts
|

Early bone apposition to hydrophilic and hydrophobic titanium implant surfaces: a histologic and histomorphometric study in minipigs

Abstract: Substantial bone apposition occurs between day 5 and day 10. The data suggest that the hydrophilic surface can provoke a slight tendency toward increased bone apposition in minipigs after 15 days. A direct comparison of two hydrophilic surfaces with varying geometries is of limited relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
69
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 30 publications
10
69
0
2
Order By: Relevance
“…This finding is similar to that of a previous clinical trial that investigated the early steps of healing in the presence of hydrophilic surfaces and found a superior degree of osseointegration after 14 days of implantation (14). Moreover, a study using mini-pig model found great bone apposition on hydrophilic surfaces 10 and 15 days post-implant placement (6). This finding corresponds very well with the same parameters assessed in dog mandibles, which showed enhanced bone formation surrounding the hydrophilic surface of implants after 14 days of healing (3).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is similar to that of a previous clinical trial that investigated the early steps of healing in the presence of hydrophilic surfaces and found a superior degree of osseointegration after 14 days of implantation (14). Moreover, a study using mini-pig model found great bone apposition on hydrophilic surfaces 10 and 15 days post-implant placement (6). This finding corresponds very well with the same parameters assessed in dog mandibles, which showed enhanced bone formation surrounding the hydrophilic surface of implants after 14 days of healing (3).…”
Section: Discussionsupporting
confidence: 90%
“…Hydrophilic implant surfaces account for faster wettability, favoring cell-implant contact, the initial phases of wound healing and a cascade of events leading to the osteogenesis (3). At the end, bone apposition increase bone-implant contact (BIC) (4) and improve bonding strength during the early stages of bone repair (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasak C found that substantial bone apposition occurred between day 5 and 10 after submerged healing of implants. 26 Kohal RJ confirmed retarded cell proliferation on the TiUnite V R surface during the first 7 days. 27 Therefore, the initial 7 days were important for osseointegration.…”
Section: Discussionmentioning
confidence: 93%